(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Increased selenium supplementation has been implicated in diabetes mellitus via peroxisome-proliferator-activated-receptor-gamma-coactivator-1-alpha (PGC-1α) associated pathways. This study was designed to investigate the effect of selenium supplementation on PGC-1α and glucose-6-phosphatase (G6Pase) as well its likely hepato toxicity in male Wistar rats. Animals were randomly divided into 3 groups (n=10/group) and treated orally with water (0.2ml - group 1) or selenium (25µg/day -group 2; 50µg/day - group 3) for 28 and 56days, respectively. Thereafter, blood samples were collected and estimated for glucose, alkaline-phosphate (ALP), gamma-glutamyltransferase (GGT) and aspartate-aminotransferase (AST). Liver homogenates were analyzed for PGC-1α and G6Pase activity. Significant dose-dependent increases in blood glucose, hepatic PGC-1α and G6Pase activities were observed on days 28 and 56 in selenium groups compared to group 1. Serum GGT activity increased in both selenium groups on day 28 however, on day 56 values in group 2 were reduced and increased in group 3, respectively. Compared to control ALP reduced in selenium groups while AST was not significantly different. This study suggests that selenium supplementation increases hepatic peroxisome-proliferator-activated-receptor-gamma-coactivator-1α and glucose-6-phosphatase activity leading to a likely increase in hepatic glucose output. It also shows that though selenium supplementation at the doses used maybe nontoxic to hepatocytes, it may however exert potential toxicity on the biliary tract